2009
DOI: 10.1093/jac/dkn531
|View full text |Cite
|
Sign up to set email alerts
|

Influence of liver fibrosis stage on plasma levels of efavirenz in HIV-infected patients with chronic hepatitis B or C

Abstract: Therapeutic drug monitoring may be of interest in cirrhotic patients more at risk of side effects due to efavirenz overdosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
0
13
2
Order By: Relevance
“…13.0%, respectively). In studies from largely Caucasian populations, high efavirenz concentrations (> 4.0 mg/L) have been reported in 13.1–18.9% of participants . By contrast, a study of 80 South African patients, with a median efavirenz concentration of 3.98 mg/L, found that the proportion of patients with high efavirenz concentrations was 40% .…”
Section: Discussionmentioning
confidence: 94%
“…13.0%, respectively). In studies from largely Caucasian populations, high efavirenz concentrations (> 4.0 mg/L) have been reported in 13.1–18.9% of participants . By contrast, a study of 80 South African patients, with a median efavirenz concentration of 3.98 mg/L, found that the proportion of patients with high efavirenz concentrations was 40% .…”
Section: Discussionmentioning
confidence: 94%
“…6,7,15,16 Other groups have found an association with female sex and antiretroviral-naïve patients undergoing their first regimen, 11 or if their regimen contains a protease inhibitor. 17 Lamivudine and ritonavir have also been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, up to 20% of patients exhibit plasma levels of efavirenz that exceed the therapeutic range. 15 …”
Section: Discussionmentioning
confidence: 99%
“…However, administration of these medications in this setting is challenging because of the alteration of hepatic metabolism and the risk of drug-induced liver injury [170]. Of note, hepatic metabolism of NNRTIs, particularly efavirenz, is impaired in coinfected patients with cirrhosis, and a similar effect has also been observed for protease inhibitors [171].…”
Section: Management Of Hiv Patients Coinfected With Hcv And/or Hbv Inmentioning
confidence: 99%